Analysis and Design Of Multistory Apartment Building Using ETABS (International Journal of Engineering and Computer Science, 2017)
Practical knowledge is an important and essential skill required by every engineer. For obtaining this skill, an apartment building is analysed and designed, Located in Latur, Maharastra with (B+G+10) storeys having a car parking facility provided at basement floor. The building has a shear wall around the lift pit. The modelling and analysis of the structure is done by using ETABS and the designing was done. Design of slab, stair case and an isolated footing are done manually. The design methods involves load calculations manually and analysing the whole structure by ETABS. The design methods used in ETABS are limit state design confirming to IS code of practice.Along with analysing and designing of this building, construction sites were also visited.